Strengthening Youth Character Through Scout With Outdoor Activities - Indra Jati Kusuma; Bambang Budi Raharjo; Harry Pramono; Sulaiman Sulaiman; Kuat Leksono; Arfin Deri Listiandi (International Conference on Science, Education, and Technology, 2021)
The impact of globalization, promiscuity, lack of supervision and moral development are the causes of character decline. It is necessary to instill character education for youth in various environments early. This study aims to analyze how scouting activities with activities outside the classroom can strengthen the character of adolescents, as well as how the supporting and inhibiting factors are. The research design used is descriptive qualitative, with a case study approach. This research was conducted at the Secretariat of the Pramuka Organization Kwaran DKR Kedungbanteng Banyumas. Data collection techniques using observation techniques, interviews, and documentation. The sampling technique in this study used purposive sampling. The validity of the data was tested by using the data triangulation technique. Data analysis used the Miles and Huberman model. The conclusion, that is found that scouting activities through activities outside the classroom can strengthen character, according to the values ​​contained in Dasadharma and Tri Satya. There are supporting factors such as: activities are fun and exciting, flexible, comfortable and don't feel burdened. While the inhibiting factors such as: a bad environment, busy coaches who are already working, parental permission, economic factors, transportation and the COVID-19 pandemic which have hampered the activities of the Kedungbanteng Branch Work Council.